Mechano-chemical oxidation of arsenopyrite. (September 2019) - Koroznikova, Larissa; McKnight, Stafford; Veder, Jean-Pierre; Giri, Jason; Palaniandy, Samayamutthirian; Williams, Gordon
Highlights: Mechano-chemical activation resulted in oxidation of arsenopyrite using water and hydrogen peroxide. Arsenic dissolution achieved at neutral starting pH, at 50 °C under oxidative conditions. Analysis demonstrates the production of soluble and amorphous products as a result of mechano-chemical processing. Mechano-chemical activation increases with milling time. Abstract: This paper presents the results from the investigation of arsenopyrite oxidation via mechano-chemical activation, using a stirred mill. Water and hydrogen peroxide were chosen as the lixiviant and oxidant, respectively, and maintained at a relatively low temperature (50 °C). The milling media size, mill speed, slurry percent solids and amount of H2 O2 added were all kept constant throughoust these experiments. The only operational variable for this investigation was the milling time, which results in increasing levels of specific energy provided by the mill. The products of activated arsenopyrite are characterised in terms of phase composition, particulate and structural characteristics, along with reactivity. Mechano-chemical activation of arsenopyrite under oxidizing conditions shows a maximum dissolution of around 9 wt% for iron and 7 wt% for arsenic after 2 h of milling. After 3 h of milling, the main phase present is found to be amorphous in nature.